2018
DOI: 10.1186/s13012-018-0800-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of a course to build core competencies in implementation practice

Abstract: BackgroundFew training opportunities are available for implementation practitioners; we designed the Practicing Knowledge Translation (PKT) to address this gap. The goal of PKT is to train practitioners to use evidence and apply implementation science in healthcare settings. The aim of this study was to describe PKT and evaluate participant use of implementation science theories, models, and frameworks (TMFs), knowledge, self-efficacy, and satisfaction and feedback on the course.MethodsPKT was delivered to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 39 publications
2
94
0
1
Order By: Relevance
“…In 2015, Implementation Science expressed a renewed interest in research describing and critically appraising D&I training initiatives [ 52 ]. Since this editorial, several descriptive and/or evaluative articles on D&I CBIs have been published [ 18 , 47 , 49 , 57 , 58 ], but for those working in D&I to gain a more detailed understanding of the evidence-base, a field-wide perspective of the published literature is required [ 59 ]. A useful starting point to address this gap is through the review and documentation of D&I CBIs that have been written up in the academic literature.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Implementation Science expressed a renewed interest in research describing and critically appraising D&I training initiatives [ 52 ]. Since this editorial, several descriptive and/or evaluative articles on D&I CBIs have been published [ 18 , 47 , 49 , 57 , 58 ], but for those working in D&I to gain a more detailed understanding of the evidence-base, a field-wide perspective of the published literature is required [ 59 ]. A useful starting point to address this gap is through the review and documentation of D&I CBIs that have been written up in the academic literature.…”
Section: Introductionmentioning
confidence: 99%
“…and content delivery components (didactic, on-site visits, mentoring, etc.) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…The core competencies framework presented in this study covers most of the competencies that have been identified from HIC settings,4–8 but it differs in its emphasis on contexts, health systems, ethics, equity issues, communication and advocacy skills (while the other frameworks emphasise IR theories, methods and designs). This difference may reflect how IR is viewed differently in LMIC settings compared with HICs.…”
Section: How Does This Framework Of Core Competencies In Ir For Lmicsmentioning
confidence: 99%
“…A review of the literature yielded six relevant articles describing competencies in IR4–9; all of these focused on IR in high-income countries (HICs) except one, the UNICEF, United Nations Development Programme (UNDP), World Bank and WHO Special Programme for Research and Training in Tropical Diseases (TDR) IR toolkit,9 which identified broad learning domains for IR researchers in LMICs, but did not explicitly define competencies under these domains. Four articles identified competencies for IR education and training programme in HICs,4–7 one of which defined four competencies that were focused exclusively on the conduct of IR,4 while the other three included competencies covering skills required in all phases of IR, including the pre-IR phase (eg, planning of IR) and post-IR phase (eg, disseminating IR results) 5–7.…”
Section: Introductionmentioning
confidence: 99%